In-situ observation of the interaction of {101¯2}a deformation twinning with 18R long period stacking ordered precipitates in an Mg-5Gd-3.5Ga (at.%) as-cast alloy. (15th March 2022) - Li, Kaixuan; Zhuang, Yuanlin; Zhao, Ligong; Zhao, Dongshan; Zheng, He; Jia, Shuangfeng; Zhang, Ying; Zhao, Peili; Gui, Jianian; Wang, Jianbo
Abstract: We have achieved direct observation of the interaction between { 10 1 ¯ 2 } a deformation twinning and 18R long period stacking ordered (LPSO) structures in an Mg-5Gd-3.5Ga (at.%) as-cast alloy through in-situ compression experiments of submicron-sized pillars, and the hinderance of LPSO structures or stacking faults (SFs) to twinning was revealed from submicron scale to atomic scale. We found that thick LPSO plates effectively retard the twinning propagation in the direction of perpendicular to the LPSO basal plane. As the spacing between LPSO structures decreased, twin propagation was more suppressed. In addition, although twinning can easily pass through low-density SFs, the step of twin boundaries on both sides of SFs at atomic scale also exhibits resistance of SFs to twinning. The propagation process of twinning was observed in real-time by in-situ technique, and further discussion of the strengthening effect of LPSO structures on suppressing the growth of twinning. Graphical abstract: Image, graphical abstract